Pengaruh Consumer Decision terhadap Peningkatan Pemesanan Online Tiket Bioskop pada Aplikasi TIX.ID (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to understand how Consumer Decisions affect the growth of online bioskop sales through the TIX.ID application. The variables examined include Website Quality, Product Factors, Customer Relationship, and Brand Equity. This study employs a quantitative approach using the berganda regression analysis technique with respect to 140 TIX.ID users.The study's findings indicate that the keempat variable has a significant impact on consumer behaviour, either simultaneously or in parallel. Website Quality, Product Factors, Customer Relationship, and Brand Equity variables all contribute to Brand Equity significant impact. This model can explain 61.4% of consumer behaviour. This study contributes to digital marketing strategies and online tiket transaction platforms.